Readers' perception level towards UMPH magazine among students of public institutions of higher learning (IPTA) in Klang Valley / Laila Sofra Abdullah Tahir - Abdullah Tahir, Laila Sofra (Faculty of Business and Management, 2006)
The main objective of this research was to explore whether there is still having the readers read UMPH and focus to the magazine components of UMPH magazine. The respondent of this study was students of Public Institutions of Higher Learning (IPTA) in Klang Valley. Hundred questionnaires had been distributed among students in Klang Valley. The researcher had used convenience sampling as the sampling technique.